Glycemic index and glycemic load of common fruit juices in Thailand - Chonnikant Visuthranukul; Pichet Sampatanukul; Suphab Aroonparkmongkol; Pathama Sirimongkol; Sirinuch Chomtho (BMC, 2022)
Abstract Background The glycemic index (GI) reflects body responses to different carbohydrate-rich foods. Generally, it cannot be simply predicted from the composition of the food but needs in vivo testing. Methods Healthy adult volunteers with normal body mass index were recruited. Each volunteer was asked to participate in the study center twice in the first week to consume the reference glucose (50 g) and once a week thereafter to consume the study fruit juices in a random order. The study fruit juices were Florida orange juice, Tangerine orange juice, Blackcurrant mixed juice, and Veggie V9 orange carrot juice which were already available on the market. The serving size of each fruit juice was calculated to provide 50 g of glycemic carbohydrate. The fasting and subsequent venous blood samplings were obtained through the indwelling venous catheters at 0, 15, 30, 45, 60, 90, and 120 min after the test drink consumption and immediately sent for plasma glucose and insulin. GI and insulin indices were calculated from the incremental area under the curve of postprandial glucose of the test drink divided by the reference drink. Glycemic load (GL) was calculated from the GI multiplied by carbohydrate content in the serving size. Results A total of 12 volunteers participated in the study. Plasma glucose and insulin peaked at 30 min after the drink was consumed, and then started to decline at 120 min. Tangerine orange juice had the lowest GI (34.1 ± 18.7) and GL (8.1 g). Veggie V9 had the highest GI (69.6 ± 43.3) but it was in the third GL rank (12.4 g). The insulin responses correlated well with the GI. Fructose to glucose ratio was inversely associated with GI and insulin responses for all study fruit juices. Fiber contents in the study juices did not correlate with glycemic and insulin indices. Conclusions The GIs of fruit juices were varied but consistently showed a positive correlation with insulin indices. Fruit juices with low GI are a healthier choice for people with diabetes as well as individuals who want to stay healthy since it produces more subtle postprandial glucose and insulin responses.